2009
DOI: 10.5324/nje.v18i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dispensing of codeine is associated with high consumption of benzodiazepines

Abstract: Aims: Our objective was to explore the use of codeine analgesics in individual patients in Norway, giving special attention to the 10% who consume the highest amounts. Methods: We retrieved data from the Norwegian Prescription Database on patients who were dispensed at least one codeine analgesic prescription during 2006. We looked at age and gender specific 1-year periodic prevalence. The 10% of codeine users who were prescribed the highest amounts of the drug that year were further characterized. Age and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…48,49 Among patients with noncancer pain, in particular, concomitant use of BZD was associated with more total months of prescribed opioid, higher mean daily doses, and a greater risk of a psychogenic chronic pain diagnosis and alcohol abuse/dependence. 48 Similarly, Bachs et al 50 found that users who were dispensed the highest doses of codeine (according to prescription records) were significantly more likely to use high doses of BZDs as well. In fact, BZD use was a stronger predictor of future prescription opioid use than musculoskeletal or chronic pain.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 96%
“…48,49 Among patients with noncancer pain, in particular, concomitant use of BZD was associated with more total months of prescribed opioid, higher mean daily doses, and a greater risk of a psychogenic chronic pain diagnosis and alcohol abuse/dependence. 48 Similarly, Bachs et al 50 found that users who were dispensed the highest doses of codeine (according to prescription records) were significantly more likely to use high doses of BZDs as well. In fact, BZD use was a stronger predictor of future prescription opioid use than musculoskeletal or chronic pain.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 96%
“…Recent literature, however, adds to the growing evidence that these substances have a similar potential for negative effects as traditional benzodiazepines [20][21][22]. Still we wanted to restrict our analysis to the prescription of the traditional benzodiazepines, which constitute a better documented marker of an addictive use pattern [14,20,23].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of prescription records, Bachs et al (2008) found that those codeine users dispensed the highest amounts of the opioid, were significantly more likely to be co-using large amounts of BZDs. Using a more determinate method, Heltsey et al (2011) found that 15.7% of oral fluid specimens from 6,441 U.S. pain clinic patients were positive for benzodiazepine drugs.…”
Section: The Co-abuse Of Benzodiazepines and Opioids In Humansmentioning
confidence: 99%